Salvaging cochlear implant after wound infection: Well worth a try. (4th July 2017) - Sharma, Shalabh; Gupta, Anandita; Bhatia, Khyati; Lahiri, Asish Kumar; Singh, Satinder
Abstract : Background : Cochlear implant (CI)-related wound infections are known to happen even years after the implant procedure and present a challenging clinical situation. Due to the formation of biofilm on the implant surface such infections are difficult to eradicate. Invariably explantation of the device is required for wound healing. Method : A 10-year-old patient presented with recurrent CI-related wound infection 8 years after implantation. The implant was salvaged with wound debridement and treating it with tea tree oil which is known for its biofilm eradicating properties. It was then covered with double layer of vascularised soft tissue. Combination of intravenous vancomycin and oral rifampicin known for their efficacy in biofilm-related infection was also used. Results : The implant could be salvaged using this novel technique of treating the implant with a biofilm eradicating agent, wound debridement, double layer vascularised soft tissue cover, and long-term antibiotics. Conclusion : Agents having anti-biofilm activity when used in conjunction with surgical debridement and judicious antimicrobial therapy can be used for salvaging the implant and limiting the morbidity associated with these infections.